Isochronous Sequential Presentation Helps Children Orient Their Attention in Time - Johnson, Katherine A.; Bryan, Marita; Polonowita, Kira; Decroupet, Delia; Coull, Jennifer T. (Frontiers in Psychology, 2016)
Knowing when an event is likely to occur allows attentional resources to be oriented towards that moment in time, enhancing processing of the event. We previously found that children (mean age 11 years) are unable to use endogenous temporal cues (line length) to orient attention in time, despite being able to use endogenous spatial cues (arrows) to orient attention in space. Arrow cues, however, may have proved beneficial by engaging exogenous (automatic), as well as endogenous (voluntary), orienting mechanisms. We therefore conducted two studies in which the exogenous properties of visual temporal cues were increased, to examine whether this helped children orient their attention in time. In the first study, the location of an imperative target was predicted by the direction of a left or right spatial arrow cue while its onset was predicted by the relative duration of a short or long temporal cue. To minimise the influence of rhythmic entrainment in the temporal condition, target onset time (500ms/1100ms) was deliberately chosen so as not to precisely match the duration of the temporal cue (100ms/400ms). Targets appeared either at cued locations/onset times (valid trials) or at unexpected locations/onset times (invalid trials). Adults’ response times were significantly slower for invalid versus valid trials, in both spatial and temporal domains. Despite being slowed by invalid spatial cues, children (mean age 10.7 years) were unperturbed by invalid temporal cues, suggesting that these duration-based temporal cues did not help them orient attention in time. In the second study, we enhanced the exogenous properties of temporal cues further, by presenting multiple temporal cues in an isochronous (rhythmic) sequence. Again, to minimise automatic entrainment, target onset did not match the isochronous interval. Children (mean age 11.4 years), as well as adults, were now significantly slowed by invalid cues in both the temporal and spatial dimension. The sequential, as opposed to single, presentation of temporal cues therefore helped children to orient their attention in time. We suggest that the exogenous properties of sequential presentation provide a temporal scaffold that supports the additional attentional and mnemonic requirements of temporal, as compared to spatial, processing.